Comparing GNSS TEC data from the African continent with IRI-2016, IRI-Plas, and NeQuick predictions. Issue 7 (1st April 2022) - Liu, Jialong; Jia, Xiaolin; Zhu, Yongxing; Xu, Jin; Fu, Junsheng; Zhang, Ruibin; He, Yanwei
Abstract: There are special ionospheric phenomena in the equatorial and South African region, e.g., equatorial plasma bubbles and broadcast ionospheric model correction anomalies which result in unique ionospheric characteristics. In this paper, we analyze the ionospheric characteristics of the experimental region using the latest GNSS dual-frequency real-world data from 2014 to 2020. This is then used as a benchmark to analyze the performance of IRI-2016, IRI Plas-2017, and NeQuick 2 empirical models and their electron content distribution at different altitudes. Finally, the correlation between the electron content of the African region and the solar activity parameters is explored. The results show that:①The annual variation of electron content in the far equatorial region does not have obvious spring-autumn bimodal structure and the electron content in the near-equatorial region is much higher than that in the far equatorial region.②Empirical models generally overestimate the electron content of the region with the IRI-2016 model consistently achieves the highest performance, the NeQuick 2 model achieves the lowest accuracy in high solar activity years, and the IRI Plas-2017 model is the worst in mid and low solar activity years.③The IRI Plas-2017 model has a relatively stable share of each layer, whereas the NeQuick 2 model has a large share of each layer influenced by solar activity. The top electron content has the largest share of the total electron content, and the plasma layer has the smallest share.④In low solar activity years, the experimental region shows solar activity and electron content correlation anomalies which are negatively correlated. Overall the EUV index has the largest correlation coefficient with the ionosphere, and the SSN has the worst correlation in this region.